Data subset for Chapter 3: Particle degradation data - Brown, Gareth; Jefferson, Bruce; MacAdam, Jitka (Cranfield University, 2022)
The particle degradation dataset for all conditions which represent data supporting 'Impact of low tmperatures on anerobic hydrolysis in passive treatment systems such as septic tanks'.
Keywords: anaerobic digestion'